In vitro prediction of in vivo skin damage associated with the wiping of dry tissue against skin. Issue 1 (13th August 2012) - Koenig, David W.; Dvoracek, Barb; Vongsa, Rebecca
<x xml:space="preserve">Abstract</x> Background The ideal gentle cleansing product is one that effectively removes soils while minimizing damage to the skin. Thus, measuring physical abrasion caused by cleansing tissues is critical to the continued development of gentle cleansing products. Current analysis of cleansing materials for skin gentleness is time consuming and requires expensive human subject testing. This report describes the development of a rapid and inexpensive bench assay for the assessment of skin abrasion caused by wiping. Methods Coefficient of friction (COF) evaluations using bench methods were compared with results from clinical studies of repeated wiping and with confocal visualizations of excised skin. A Monitor/Slip and Friction™ instrument (model 32‐06; TMI, Amityville, NY, USA) was used to measure tissue friction on simulated skin (Vitro‐Skin®, N19‐5X; IMS, Milford, CT, USA). Clinical data from a 4‐day repetitive forearm wiping study measuring transepidermal water loss (TEWL) in 30 subjects was compared with results from the bench top assay. In addition, excised skin samples were also treated using the COF bench assay and examined using confocal microscopy to visualize stratum corneum damage caused by wiping. Results Using the bench COF assay, we were able to distinguish between bath tissue codes by comparing average static friction value (ASFV) for the test codes, where lower ASFV indicated less abrasive tissue. The ASFV followed the same gentleness trend observed in the clinical study. Confocal microscopy of excised skin wiped with the same materials indicated stratum corneum damage consistent with the bench COF and clinical TEWL observations. Conclusion We observed significant correlation between bench and clinical methods for measuring skin damage caused by wiping of skin with tissue. The bench method will facilitate rapid and inexpensive skin gentleness assessment of cleansing materials.